Rethinking Subnational Taxes : A New Look At Tax Assignment - Bird, Richard (IMF Working Papers; Working Paper ;, 1999)
The assignment of revenues in most developing and transitional countries to the central government has arguably facilitated irresponsible behavior by some subnational governments. One way to relieve this problem is to strengthen subnational tax regimes. The paper proposes two approaches to accomplish such strengthening in developing countries. The first-most applicable to large countries with important regional governments-is to establish subnational value-added taxes (VATs); the second is to replace the various unsatisfactory state and local taxes imposed on business by a low-rate value-added tax levied on the basis of income (production, origin) rather than consumption (destination).